-21=-2c-15-2c+7

Simple and best practice solution for -21=-2c-15-2c+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -21=-2c-15-2c+7 equation:



-21=-2c-15-2c+7
We move all terms to the left:
-21-(-2c-15-2c+7)=0
We add all the numbers together, and all the variables
-(-4c-8)-21=0
We get rid of parentheses
4c+8-21=0
We add all the numbers together, and all the variables
4c-13=0
We move all terms containing c to the left, all other terms to the right
4c=13
c=13/4
c=3+1/4

See similar equations:

| z2–25=0 | | 10x-5=6x+5 | | 2x+3=1000 | | X+5=19-3x | | 3 / 1 + 9 - y = 0 | | -75=-25x | | 29y^2-36y=0 | | 3x+7=6x-6 | | 11+9s=50 | | 5(-4+2)-5x-3=257 | | 3b=-56 | | 20+10x=15x+15+5 | | 48+56+3c=11c+56 | | 48+56+3c=11c+6 | | 7(-8+6m)-3m=-290 | | 3x^-12x+7=0 | | -4x+12=6x | | 32-6=-n | | 3x2-12x+7=0 | | 4.4=-t/1.5 | | 553.51=240+1.07x | | X-(3x-2)=2x+4 | | -3+6n=7n-1 | | (4x+3)+(8x+3)=180 | | (4x+3)+(8x+3)=90 | | (4x+3)=(8x+3)+90 | | -2-4k=k-2-2k | | 36-3m=-1m-(-8) | | 4(p+20)=1/5(20p+400) | | 5(k+2)=45 | | 33=12r=3(9-r) | | 7x−1=8x−6 |

Equations solver categories